Beneficial effects of intraperitoneally administered alpha-tocopheryl acetate on the levels of lipid peroxide and activity of glutathione peroxidase and superoxide dismutase in skin, blood and liver of thermally injured guinea pigs - Naziroglu, M; Kökçam, I; Yilmaz, S (Karger, 2003)
The aim of this study was to investigate the effects of intraperitoneal alpha-tocopheryl acetate administration on concentration of lipid peroxide (as malonyldialdehyde, MDA), reduced glutathione (GSH), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) in plasma, red blood cells (RBC), skin and liver of thermally injured guinea pigs. MDA levels in the plasma, skin and liver were increased at the 15th min after the thermal injury compared to the control group. However, they were significantly lower in the alpha-tocopheryl-acetate-treated groups than both control and thermally injured groups from the 15th min to the 6th day. SOD activity of the skin and RBC and vitamin E levels in the plasma were significantly decreased between the 15th min and 6th day and then both parameters, i.e. SOD and vitamin E, were significantly increased by alpha-tocopheryl acetate administration. GSH-Px activity in the skin was also significantly decreased in groups from the 15th min to the 6th day, whereas it remained unchanged by the alpha-tocopheryl acetate administration. On the other hand, GSH-Px activity and GSH levels in the RBC remained the same during both thermal injury and alpha-tocopheryl acetate administration. In conclusion, we observed that the intraperitoneal administration of alpha-tocopheryl acetate protects the skin against thermal injury, which suggests that it may be due to the upregulation of enzymatic antioxidants. Copyright (C) 2003 S. Karger AG, Basel.
Keywords: thermal injury; lipid peroxidation; superoxide dismutase; vitamin E